Persistence of beak and feather disease virus (BFDV) infection in wild Crimson Rosellas (Platycercus elegans). (2nd October 2019) - Martens, Johanne M.; Stokes, Helena S.; Eastwood, Justin R.; Raidal, Shane R.; Peters, Andrew; Berg, Mathew L.; Walder, Ken; Magrath, Michael J. L.; Bennett, Andrew T. D.
ABSTRACT: Beak and feather disease virus (BFDV) is a globally distributed pathogen of psittacine birds. In Australia, it is thought to be the dominant pathogen of Psittaciformes, and it is listed as a 'key threatening process to biodiversity'. Infection with BFDV can cause serious and often fatal disease. However, knowledge on BFDV infection persistence in wild hosts is scarce. We investigated this in 55 wild Crimson Rosellas ( Platycercus elegans ) in Victoria, Australia, which were trapped and tested two to five times during 14 years of study. We analysed blood and feather samples for BFDV and antibodies. We then quantified infection persistence in 17 individuals that were BFDV-positive (BFDV+) during at least one capture, and that were recaptured at intervals of 0.5 months to 5.9 years. Birds that were BFDV+ when first caught were likely to also be BFDV+ if recaptured within the following five months (80%, 4/5), but this rate declined to only 8.3% of birds (1/12) that were recaptured more than five months after initial capture. BFDV was detected in feathers of 44.4% (4/9) of birds that were BFDV+ in blood upon initial capture, and 88.9% (8/9) of these individuals showed an immunological response to infection upon recapture. Viral load varied between captures and individuals. Our data indicate that P. elegans can clear BFDV from their blood, and provide new estimates for the duration of chronic BFDV infection in wild parrots. These findings can aid wildlife disease management and species conservation.